Warm-keeping antibacterial air layer fabric and preparation process thereof

By adopting specific fiber combination and treatment technology in air-layer fabrics, antibacterial microcapsules are loaded and treated with magnetron sputtering and He ion irradiation, a repairable antibacterial layer is formed, which solves the problem of insufficient warmth and antibacterial properties of existing air-layer fabrics, and achieves efficient and stable antibacterial effects and self-healing functions.

CN119553415APending Publication Date: 2025-03-04JIANGSU YOUBIAO FIBER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411797777.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing air-layer fabrics have poor warm and antibacterial properties, and their antibacterial effects are also weaker. As time goes by and the number of uses increases, their antibacterial properties and warmth will be weakened.

Method used

Warm and antibacterial air-layer fabrics woven with flexible lining and air-layer grey cloth are loaded with antibacterial microcapsules, and antibacterial components are deposited through magnetron sputtering technology, combined with He ion irradiation treatment to form a repairable antibacterial layer.

Benefits of technology

It significantly improves the warmth and antibacterial stability of the fabric. The fabric can still maintain good antibacterial properties after multiple use and cleaning, extends the duration of the antibacterial ingredients, and achieves a self-healing effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553415A_ABST
    Figure CN119553415A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fabric preparation, in particular to a warm-keeping antibacterial air layer fabric and a preparation process thereof. The air layer fabric is formed by weaving a flexible lining gray fabric and an air layer gray fabric; the flexible lining grey cloth is obtained by spinning mulberry silk, tussah silk and castor silk through a spinning machine; the air layer grey cloth is obtained by weaving terylene, spandex and cloth conductive fibers in a seven-way air layer structure; antibacterial master batches are loaded on the surfaces and the interiors of the flexible lining gray fabric and the air layer gray fabric, and the distribution density of the antibacterial master batches is 35-60 g / m < 2 >; the preparation technology comprises the following steps of S1, weaving, S2, blank fixing, S3, dyeing, S4, drying, S5, shearing and S6, shaping. According to the configuration mode, the polyester, the spandex and the cloth conductive fibers are designed into an air interlayer by adopting a special structure, and the fabric has warm-keeping and antibacterial capabilities on multiple layers through seven-way configuration, so that the warm-keeping and antibacterial effects of the fabric are further optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabric preparation, and in particular to a warm-keeping and antibacterial air layer fabric and a preparation process thereof. Background Art

[0002] Air layer fabric refers to fabric that contains a large number of fibers or tiny pores inside, and a layer of gas is formed inside and outside, forming a thermal insulation effect. When the human body wears clothes made of air layer fabric to move, the air layer can form a thermal insulation space of a certain thickness around the body, reducing the loss of external heat, thereby improving the wearer's thermal insulation effect; air layer fabric consists of three layers: inner layer, middle layer and outer layer, and the air layer in the middle forms a sandwich structure; air layer fabric is not easy to wrinkle, has good rebound and thermal insulation effects, so it is widely used in clothing manufacturing; comfort is one of the most important standards for clothing fabrics; air layer fabrics are beautiful, elastic, and have strong moisture absorption and perspiration functions, so they are very popular.

[0003] In the prior art, most air layer fabrics have poor thermal insulation and antibacterial properties, and the durability of the antibacterial effect is poor. The antibacterial and thermal insulation properties of the air layer fabric will be weakened over time and with the number of times the fabric is used. In order to solve the above problems, the present invention proposes a thermal insulation and antibacterial air layer fabric with self-repairing effect and recyclable, and a preparation process thereof. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a warm and antibacterial air layer fabric and a preparation process thereof.

[0005] The technical scheme of the present invention is: a warm and antibacterial air layer fabric is woven from a flexible lining fabric and an air layer fabric; the flexible lining fabric is woven from mulberry silk, tussah silk and castor silk through a weaving machine; the air layer fabric is woven from polyester, spandex and conductive fiber in a seven-way air layer structure; the surface and interior of the flexible lining fabric and the air layer fabric are loaded with antibacterial masterbatch, and the distribution density of the antibacterial masterbatch is 35-60g / m 2 .

[0006] Furthermore, the warm and antibacterial air layer fabric according to claim 1 is characterized in that the yarn configuration of the seven air layers is as follows: the yarns of the seven air layers are sequentially recorded as the first to seventh routes from the outside to the inside, the first, second and third routes are the outer layer, the fourth route is the middle layer, the fifth, sixth and seventh routes are the inner layer, and the outer layer and the inner layer are symmetrically arranged along the middle layer; the coil length: the second and sixth routes are 5 to 20 cm / 100 stitches, the third and fifth routes are 22 to 28 cm / 100 stitches, and the first, fourth and seventh routes are 30 to 35 cm / 100 stitches;

[0007] Description: The above configuration adopts a special structural design to form an air layer in the fabric. This structural design of the first route as the surface layer, and from the outside to the inside, the secondary surface layer, the first connecting layer, the hollow layer, the second connecting layer, the secondary inner layer, and the seventh route as the inner layer can effectively reduce heat loss and improve the warmth retention of the fabric. The seven-route configuration further optimizes the antibacterial stability of the air layer fabric and improves its warmth retention and antibacterial effect.

[0008] Furthermore, the first, fourth and seventh paths are connected with spandex, the third and fifth paths are connected with polyester, and the second and sixth paths are connected with cloth conductive fibers; the linear density of the cloth conductive fibers is 15-25D, and the number of holes is 1-5F; the linear density of the polyester is 30-50D, and the number of holes is 50-80F; the linear density of the spandex is 20-35D, and the number of holes is 5-10F;

[0009] Description: The polyester yarn forms a continuous thermal insulation layer in the fabric, and the spandex gives the fabric good elasticity, so that the fabric can better fit the body and reduce air convection, thereby indirectly improving the thermal insulation effect. The conductive fiber is evenly distributed in the fabric. The above combination can provide comprehensive antibacterial protection for the fabric, so that the fabric has thermal insulation and antibacterial capabilities at multiple levels, further enhancing the thermal insulation and antibacterial capabilities of the fabric.

[0010] Furthermore, the preparation method of the antibacterial masterbatch is as follows: first, lyocell is immersed in a composite solution of 5 to 10 mol / L at a mass ratio of 1:2 to 6, the immersion temperature is 80 to 90°C, and the immersion time is 2 to 5 hours to obtain pretreated lyocell; the composite solution is obtained by stirring and mixing zinc nitrate hexahydrate and ethanol solution at a volume ratio of 1:1.5 to 3;

[0011] Then, 2-5 mol / L caustic soda solution is added to adjust the pH of the pretreated lyocell to 7.5-8, rinse with water 2-3 times, and perform the first refinement treatment by supersonic particle bombardment at an airflow pressure of 1.8-2.4 MPa after vacuum drying. After repeating the treatment 3-5 times, prepare a composite liquid according to the mass ratio of lyocell to the composite liquid of 1:2.5-4, soak in the composite liquid at 30-40°C for 20-40 minutes, and obtain lyocell loaded with the composite liquid through drying; the composite liquid is a graphene oxide solution with a mass concentration of 5-8 mg / mL and a mineral oil with a mass concentration of 1-1.5% in a volume ratio of 1:0.2-0.3; the drying temperature is 50-70°C, and the drying time is 15-20 minutes;

[0012] Then, 2-5 mol / L caustic soda solution is added to adjust the pH value of the solvent-spun fiber loaded with the composite liquid to 8.5-9, rinsed with clean water 1-2 times, vacuum dried, and subjected to a second refinement treatment by supersonic particle bombardment at an airflow pressure of 3.6-4.2 MPa. After repeating the treatment 1-3 times, the repairable antibacterial microcapsules are deposited on the surface of the solvent-spun cellulose by magnetron sputtering to obtain the antibacterial masterbatch; during the magnetron sputtering process, the argon flow rate is 35-40 sccm, the air pressure of the vacuum chamber is 0.4-0.8 Pa, the magnetron sputtering temperature is 22-30°C, the magnetron sputtering power is 180-220 W, the deposition amount is 2-5 nm / min, and the deposition time is 30-60 s;

[0013] The supersonic particle bombardment parameters are as follows: the sprayed particles are silver particles, the diameter of the sprayed particles is 20-30 μm, the bombardment time is 3-10 min, the air flow temperature is 40-60° C., and the bombardment distance is 10-20 mm;

[0014] Description: By soaking the soluble cellulose in a composite solution composed of zinc nitrate hexahydrate and ethanol solution and pretreating it at a specific temperature and time, the surface activity and adsorption capacity of the soluble cellulose can be enhanced. Zinc nitrate hexahydrate itself also has antibacterial properties. The soaked soluble cellulose has better wash resistance and loading capacity. Mineral oil can improve the bonding strength between graphene oxide and soluble cellulose. This stronger bonding force helps prevent graphene oxide from falling off or dispersing during use, thereby maintaining its long-term effectiveness. Caustic soda can destroy the hydrogen bonds in the cellulose molecules and make its structure loose, which is beneficial to the subsequent dissolution and spinning process. Caustic soda can also remove impurities in cellulose and improve the purity of the fiber. The antibacterial microcapsules can release the internal antibacterial components for repair when damaged, thereby maintaining a long-term antibacterial effect. Magnetron sputtering technology can accurately control the deposition position and thickness of the antibacterial microcapsules and improve the overall performance of the antibacterial masterbatch.

[0015] Furthermore, the preparation method of the repairable antibacterial microcapsule is as follows: first, a spherical hollow nano titanium powder with a particle size of 120 to 180 μm is prepared by a soft template method, and then an antibacterial liquid is sprayed on the surface of the spherical hollow nano titanium powder to obtain an antibacterial layer with a thickness of 5 to 10 μm, and then a curing treatment is performed at a temperature of 100 to 120° C. for 5 to 10 minutes, and then a repair agent A is sprayed on the surface of the antibacterial layer through a spray template A and a repair agent B is sprayed through a spray template B in sequence, wherein the antibacterial liquid comprises, by mass percentage, 65 to 75% of nano silver gel, 5 to 10% of disodium hydrogen phosphate and the remainder of sodium carboxymethyl cellulose; the repair agent A comprises, by mass percentage, 12 to 25% of nano zinc particles, 5 to 10% of carbomer, 5 to 10% of chitosan and the remainder of caprylic acid glyceride; the repair agent B is an aqueous polyurethane; the spray template A and the spray template B are each composed of a plurality of 1 cm 2 The unit templates are composed of 2×2 openings evenly distributed on each unit template, and the opening diameter of the spray template A is 0.2-0.3 cm, and the opening diameter of the spray template B is 0.15-0.25 cm; the spraying method is: first spraying a layer of repair agent A inside the opening of the spray template A, then removing the spray template A and adjusting the position of the spray template B so that its openings are respectively located at the center of the 2×2 openings of the spray template A, and then spraying a layer of repair agent B inside the opening of the spray template B;

[0016] During the spraying process, the distance between the nozzle and the spherical hollow nano titanium powder is 25 to 45 cm, and the spraying pressure is

[0017] 0.2~0.5MPa.

[0018] Description: The spraying method can ensure that the nanosilver gel is evenly distributed on the substrate in the form of droplets. The microcapsules can release the repair agent when the shell surface is damaged, and the gel in the form of droplets may be more likely to interact with these repair agents to form a repair layer. The nanogel can be quickly and evenly dispersed in the material, and connected to the internal microstructure of the material by adsorption or fusion to form a continuous and flexible sol-gel system. This system can effectively fill the damaged area, form a high-strength and high-toughness repair interface, and achieve self-repair. The hydrophilic groups of water-based polyurethane can improve the air permeability of the microcapsules, and carbomer and sodium carboxymethyl cellulose can increase the viscosity and stability of the gel, effectively prolonging the duration of action of the antibacterial ingredients.

[0019] Furthermore, after the repair agent A is sprayed, it is placed in an irradiation box for He ion irradiation treatment, and then the repair agent B is sprayed after the treatment is completed; wherein, the irradiation energy of He ion irradiation is 350-370keV, the irradiation temperature is controlled at 440-460°C, and the injection amount is 3-5×10 16 cm-2 ;

[0020] Description: He ion irradiation treatment can improve the wear resistance, water resistance and washability of the fabric, so that the fabric can still maintain good antibacterial properties after multiple uses and washings. By spraying these two materials in sequence, a composite antibacterial layer can be formed on the surface of nano-titanium. In addition, He ion irradiation treatment can obtain a smooth surface with low defect density, low chemical activity and optimized stress state under high-energy and high-flux He plasma irradiation, thereby improving the comprehensive performance of the material and laying a good foundation for subsequent coating and film coating processes. It can also further activate the surface activity of nano-titanium and promote its interaction with caprylic decanoic acid glyceride, thereby enhancing the overall antibacterial effect.

[0021] The present invention also provides a preparation process of a warm and antibacterial air layer fabric, comprising the following steps:

[0022] S1. Weaving: Place equal weights of polyester, spandex and conductive fabric on a three-position double-sided circular knitting machine and weave them in a double-sided fiber alignment method to form a woven fabric with a gram weight of 200-240g / m 2 The air layer fabric is formed by sewing the flexible lining fabric and the air layer fabric to obtain a composite fabric;

[0023] S2, setting the blank: setting the composite blank obtained in step S1 at a temperature of 200-240° C. for 30-60 seconds to obtain a blank of a predetermined shape;

[0024] S3, dyeing: placing the predetermined parison of step S2 in a citric acid dyeing liquid at 30-50°C, first heating to 90-98°C, keeping warm for 15-30 minutes, to obtain system I; cooling system I to 60-75°C and keeping at this temperature for 15-30 minutes, during which time, adding insurance powder accounting for 5-8% of the weight of the composite grey cloth, to obtain system II; cooling system II to 40-60°C, adding softener, and keeping warm for 20-40 minutes;

[0025] S4, drying: the fabric treated in step S3 is taken out, cleaned with water, and dried at 60-80°C;

[0026] S5, shearing: performing single-side shearing on the fabric processed in step S4;

[0027] S6, shaping: the fabric treated in step S5 is opened and shaped to obtain a warm and antibacterial air layer fabric.

[0028] Further, the softener is a hydroxyl-terminated polysiloxane emulsion;

[0029] Description: Hydroxyl-terminated polysiloxane emulsion can make fabrics soft and smooth, and can also give nonwovens surface gloss and improve their anti-wrinkle effect.

[0030] Furthermore, the parameters of the opening and setting are: the setting temperature is 150-180°C, the setting speed is 20-30m / min, and the setting time is 2-3min;

[0031] Note: The above opening width shaping parameters can achieve better shaping effects.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The configuration of the present invention uses a special structural design to form an air interlayer of polyester, spandex, and cloth conductive fibers. This structure can effectively reduce heat loss and improve the warmth retention of the fabric. The above combination method can utilize the polyester yarn to form a continuous warmth retention layer in the fabric, and the spandex gives the fabric good elasticity, so that the fabric can better fit the body and reduce air convection, thereby indirectly improving the warmth retention effect. The cloth conductive fibers are evenly distributed in the fabric, providing comprehensive antibacterial protection for the fabric. Through the seven-way configuration, the fabric has warmth retention and antibacterial capabilities at multiple levels, further optimizing the warmth retention and antibacterial effects of the fabric.

[0034] (2) The present invention refines lyocell by supersonic particle bombardment, which can significantly improve its surface roughness and specific surface area, which not only helps the graphene oxide and antibacterial microcapsules to firmly adhere to the surface of lyocell, but also increases the loading amount and release efficiency of the antibacterial components. In addition, since lyocell has strong moisture absorption and perspiration properties, it helps to regulate the human microclimate and keep the fabric dry and comfortable. In addition, the refinement treatment can also improve the mechanical properties and durability of lyocell, adjust the pH value of lyocell and load graphene oxide and repairable antibacterial microcapsules on the surface in sequence, thereby improving the antibacterial property and self-repairing effect of the air layer fabric.

[0035] (3) The present invention further improves the wear resistance, water resistance and wash resistance of the fabric by applying He ion irradiation treatment during the process of loading graphene oxide and repairable antibacterial microcapsules, so that the fabric can still maintain good antibacterial properties after multiple uses and washings. By spraying graphene oxide and repairable antibacterial microcapsules in sequence, a composite antibacterial layer can be formed on the surface of nano-titanium. He ion irradiation treatment can further activate the surface activity of nano-titanium and promote its interaction with caprylic decanoic acid glyceride in the repairable antibacterial microcapsules, thereby enhancing the overall antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1It is a schematic diagram of the air layer yarn weaving structure of the present invention;

[0037] Figure 2 This is a comparison chart of the antibacterial properties of the air layer fabrics obtained by washing 0 times in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2;

[0038] Figure 3 It is a comparison chart of the antibacterial properties of the air layer fabrics obtained by washing 100 times in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2;

[0039] Figure 4 It is a comparison chart of the antibacterial properties of the air layer fabrics obtained by washing 0 times in Example 1, Examples 6 to 15 and Comparative Examples 3 to 4 of the present invention;

[0040] Figure 5 It is a comparison chart of the antibacterial properties of the air layer fabrics obtained by washing 100 times in Example 1, Examples 6 to 15 of the present invention and Comparative Examples 3 to 4;

[0041] Figure 6 It is a comparison chart of the antibacterial properties of the air layer fabrics obtained by washing 0 times in Example 1, Examples 16 to 31 of the present invention and Comparative Examples 5 to 6;

[0042] Figure 7 It is a comparison chart of the antibacterial properties of the air layer fabrics obtained by washing 100 times in Example 1, Examples 16 to 31 of the present invention and Comparative Examples 5 to 6;

[0043] Figure 1 Middle, 1-upper stitch, 2-lower stitch, 3-interlacing point. DETAILED DESCRIPTION

[0044] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0045] Embodiment 1: A warm and antibacterial air layer fabric is woven from a flexible lining fabric and an air layer fabric; the flexible lining fabric is woven from mulberry silk, tussah silk, and castor silk by a weaving machine; the air layer fabric is woven from polyester, spandex, and conductive fibers in a seven-way air layer structure; the surface and interior of the flexible lining fabric and the air layer fabric are loaded with antibacterial masterbatch, and the distribution density of the antibacterial masterbatch is 50g / m 2 ;

[0046] The yarn configuration of the seven-way air layer is as follows: the yarns of the seven-way air layer are recorded as route ① to route ⑦ from outside to inside, route ①②③ is the outer layer, route ④ is the middle layer, route ⑤⑥⑦ is the inner layer, and the outer layer and the inner layer are symmetrically arranged along the middle layer; route ② and route ⑥ are 15cm / 100 needles, route ③ and route ⑤ are 25cm / 100 needles, route ①, route ④ and route ⑦ are 32cm / 100 needles; route ①④⑦ is connected with spandex, The third and fifth paths are connected to polyester, and the second and sixth paths are connected to cloth conductive fibers; the linear density of the cloth conductive fibers is 20D, and the number of holes is 3F; the linear density of the polyester is 40D, and the number of holes is 65F; the linear density of the spandex is 30D, and the number of holes is 8F; it can be understood that F is the number of holes in the spinneret when manufacturing chemical fibers, such as 20D / 30F, which means that the spinneret has 30 holes, in other words, it represents a bundle of 20D cloth conductive fibers, which is composed of 30 fine fibers;

[0047] It is understandable that if Figure 1 As shown, ① the route is arranged according to the sequence of lower stitch, upper stitch, upper stitch, lower stitch, upper stitch, upper stitch, and so on;

[0048] ② The route is arranged according to the upper stitch, lower stitch, upper stitch, lower stitch, ...;

[0049] ③ The route is arranged according to the sequence of upper stitch, upper stitch, lower stitch, lower stitch, upper stitch, upper stitch, and so on;

[0050] ④ The route is arranged according to the following steps: lower stitch, upper stitch, lower stitch, upper stitch, ...;

[0051] ⑤ The route is arranged according to the following steps: down stitch, down stitch, up stitch, up stitch, down stitch, down stitch, ...;

[0052] ⑥ The route is arranged according to the following steps: lower stitch, upper stitch, lower stitch, lower stitch, ...;

[0053] The seventh route is arranged in the order of upper stitch, lower stitch, lower stitch, upper stitch, lower stitch, lower stitch, ...; that is, the first route is symmetrical with the seventh route, the second route is symmetrical with the sixth route, and the third route is symmetrical with the fifth route;

[0054] When the yarn is looped from above during the interlacing process, a float is created, meaning that the yarn forms a loop above the interlacing point. This can increase the cover and thickness of the fabric because the yarn takes up more space on the surface of the fabric. The presence of floats also affects the elasticity and stretchability of the fabric, generally making the fabric softer and more flexible. When the yarn is looped from below during the interlacing process, it forms a loop on the back side of the fabric, which is usually opposite the front side of the fabric. This may make the front side of the fabric smoother because there are fewer floats on the back side; however, it may also reduce the cover and thickness of the fabric, affecting its warmth and strength.

[0055] The preparation method of the antibacterial masterbatch is as follows: firstly, lyocell is immersed in a 7 mol / L composite solution at a mass ratio of 1:4, the immersion temperature is 85°C, and the immersion time is 3.5 hours to obtain pretreated lyocell; the composite solution is obtained by stirring and mixing zinc nitrate hexahydrate and ethanol solution at a volume ratio of 1:2.2;

[0056] Then, a 4 mol / L caustic soda solution was added to adjust the pH of the pretreated lyocell to 7.7, and the lyocell was rinsed with water twice. After vacuum drying, the first refinement treatment was performed by supersonic particle bombardment at an airflow pressure of 2.1 MPa. After repeating the treatment 4 times, a composite liquid was prepared according to a mass ratio of lyocell to the composite liquid of 1:3.2, and the lyocell was immersed in the composite liquid at 35°C for 30 minutes. After drying, lyocell loaded with the composite liquid was obtained; the composite liquid was a mixture of a graphene oxide solution with a mass concentration of 6 mg / mL and a mineral oil with a mass concentration of 1.25% in a volume ratio of 1:0.25; the drying temperature was 60°C, and the drying time was 18 minutes;

[0057] Then, 3 mol / L caustic soda solution was added to adjust the pH of the lyocell loaded with the composite liquid to 8.7, rinsed with water twice, vacuum dried, and then subjected to a second refinement treatment by supersonic particle bombardment at an airflow pressure of 3.9 MPa. The other supersonic particle bombardment parameters were consistent with the first refinement treatment. After repeating the treatment twice, magnetron sputtering was used to deposit repairable antibacterial microcapsules on the surface of the lyocell to obtain the antibacterial masterbatch. During the magnetron sputtering process, the argon flow rate was 38 sccm, the air pressure of the vacuum chamber was 0.6 Pa, the magnetron sputtering temperature was 26°C, the magnetron sputtering power was 200 W, the deposition amount was 3 nm / min, and the deposition time was 45 s. Among them, the supersonic particle bombardment parameters were: the sprayed particles were silver particles, the diameter of the sprayed particles was 25 μm, the bombardment time was 7 min, the airflow temperature was 50°C, and the bombardment distance was 15 mm. The repairable antibacterial microcapsules were commercially available textile antibacterial self-repairing microcapsules.

[0058] This embodiment provides a preparation process of a warm and antibacterial air layer fabric, comprising the following steps:

[0059] S1. Weaving: Place equal weights of polyester, spandex and conductive fabric on a three-position double-sided circular knitting machine and weave them in a double-sided fiber alignment method to form a 220g / m 2 The air layer fabric is formed by sewing the flexible lining fabric and the air layer fabric to obtain a composite fabric;

[0060] S2, setting the blank: setting the composite blank obtained in step S1 at a temperature of 220° C. for 45 seconds to obtain a blank of a predetermined shape;

[0061] S3, dyeing: placing the predetermined parison of step S2 in a citric acid dyeing liquid at 40°C, first heating to 94°C, keeping warm for 22 minutes, to obtain system I; cooling system I to 68°C and keeping at this temperature for 22 minutes, during which time, adding insurance powder accounting for 7% of the weight of the composite grey cloth, to obtain system II; cooling system II to 50°C, adding a softener, and keeping warm for 30 minutes; the softener is a hydroxyl-terminated polysiloxane emulsion; the insurance powder is commercially available sodium dithionite;

[0062] S4, drying: taking out the fabric treated in step S3, washing it with water, and drying it at 70°C;

[0063] S5, shearing: performing single-side shearing on the fabric processed in step S4;

[0064] S6, shaping: the fabric treated in step S5 is opened and shaped to obtain a warm and antibacterial air layer fabric; the parameters for the opening and shaping are: shaping temperature of 165° C., shaping speed of 25 m / min, and shaping time of 2.5 min.

[0065] Example 2: Different from Example 1, the distribution density of the antibacterial masterbatch is 35g / m 2 .

[0066] Example 3: Different from Example 1, the distribution density of the antibacterial masterbatch is 60g / m 2 .

[0067] Example 4: Different from Example 1, the coil lengths are: 5 cm / 100 stitches for the ② and ⑥ routes, 22 cm / 100 stitches for the ③ and ⑤ routes, 30 cm / 100 stitches for the ①, ④ and ⑦ routes; the linear density of the conductive fiber of the cloth is 15D, and the number of holes is 1F; the linear density of polyester is 30D, and the number of holes is 50F; the linear density of spandex is 20D, and the number of holes is 5F.

[0068] Example 5: Different from Example 1, the coil lengths are: 20 cm / 100 stitches for the ② and ⑥ routes, 28 cm / 100 stitches for the ③ and ⑤ routes, and 35 cm / 100 stitches for the ①, ④ and ⑦ routes; the linear density of the conductive fiber of the cloth is 25D, and the number of holes is 5F; the linear density of the polyester is 50D, and the number of holes is 80F; the linear density of the spandex is 35D, and the number of holes is 10F.

[0069] Example 6: Different from Example 1, the lyocell is first immersed in a 5 mol / L composite solution at a mass ratio of 1:2, the immersion temperature is 80°C, and the immersion time is 2 h to obtain pretreated lyocell; the composite solution is obtained by stirring and mixing zinc nitrate hexahydrate and ethanol solution at a volume ratio of 1:1.5.

[0070] Example 7: Different from Example 1, the lyocell is first immersed in a 10 mol / L composite solution at a mass ratio of 1:6, the immersion temperature is 90°C, and the immersion time is 5 h to obtain pretreated lyocell; the composite solution is obtained by stirring and mixing zinc nitrate hexahydrate and ethanol solution at a volume ratio of 1:3.

[0071] Example 8: Different from Example 1, 2 mol / L caustic soda solution is then added to adjust the pH of the pretreated lyocell to 7.5, rinsed with clean water twice, and vacuum dried before the first refinement treatment by supersonic particle bombardment at an airflow pressure of 1.8 MPa. After repeating the treatment three times, a composite liquid is prepared according to a mass ratio of lyocell to composite liquid of 1:2.5, and the lyocell is immersed in the composite liquid at 30°C for 20 minutes. After drying, lyocell loaded with graphene oxide is obtained; the drying temperature is 50°C and the drying time is 15 minutes.

[0072] Example 9: Different from Example 1, 5 mol / L caustic soda solution is then added to adjust the pH of the pretreated lyocell to 8, rinsed with clean water 3 times, and vacuum dried before the first refinement treatment by supersonic particle bombardment at an airflow pressure of 2.4 MPa. After repeating the treatment 5 times, a composite liquid is prepared according to a mass ratio of lyocell to the composite liquid of 1:4, and the lyocell is immersed in the composite liquid at 40°C for 40 minutes. After drying, lyocell loaded with graphene oxide is obtained; the drying temperature is 70°C and the drying time is 20 minutes.

[0073] Example 10: Different from Example 1, the supersonic particle bombardment parameters are: the sprayed particles are silver particles, the diameter of the sprayed particles is 20 μm, the bombardment time is 3 min, the air flow temperature is 40°C, and the bombardment distance is 10 mm; the composite liquid is a graphene oxide solution with a mass concentration of 5 mg / mL and a mineral oil with a mass concentration of 1% mixed in a volume ratio of 1:0.2.

[0074] Example 11: Different from Example 1, the supersonic particle bombardment parameters are: the sprayed particles are silver particles, the diameter of the sprayed particles is 30 μm, the bombardment time is 10 min, the air flow temperature is 60°C, and the bombardment distance is 20 mm; the composite liquid is a graphene oxide solution with a mass concentration of 8 mg / mL and a mineral oil with a mass concentration of 1.5% mixed in a volume ratio of 1:0.3.

[0075] Example 12: Different from Example 1, 2 mol / L caustic soda solution is continued to be added to adjust the pH of the soluble cellulose loaded with graphene oxide to 8.5, rinsed once with clean water, and vacuum dried, and then subjected to a second refinement treatment by supersonic particle bombardment at an airflow pressure of 3.6 MPa. After repeating the treatment once, repairable antibacterial microcapsules are deposited on the surface of the soluble cellulose by magnetron sputtering to obtain the antibacterial masterbatch.

[0076] Example 13: Different from Example 1, 5 mol / L caustic soda solution is then added to adjust the pH of the soluble cellulose loaded with graphene oxide to 9, the solution is rinsed with clean water twice, and vacuum dried, and then a second refinement treatment is performed by supersonic particle bombardment at an airflow pressure of 4.2 MPa. After repeating the treatment three times, repairable antibacterial microcapsules are deposited on the surface of the soluble cellulose by magnetron sputtering to obtain the antibacterial masterbatch.

[0077] Example 14: Different from Example 1, during the magnetron sputtering process, the argon gas flow rate is 35 sccm, the gas pressure of the vacuum chamber is 0.4 Pa, the magnetron sputtering temperature is 22°C, the magnetron sputtering power is 180 W, the deposition amount is 2 nm / min, and the deposition time is 30 s.

[0078] Example 15: Different from Example 1, during the magnetron sputtering process, the argon gas flow rate is 40 sccm, the gas pressure of the vacuum chamber is 0.8 Pa, the magnetron sputtering temperature is 30°C, the magnetron sputtering power is 220 W, the deposition amount is 5 nm / min, and the deposition time is 60 s.

[0079] Embodiment 16: Different from Embodiment 1, in step S1, the woven fabric has a gram weight of 200 g / m 2 Air layer fabric.

[0080] Embodiment 17: Different from Embodiment 1, in step S1, the woven fabric has a gram weight of 240 g / m 2 Air layer fabric.

[0081] Embodiment 18: Different from Embodiment 1, in step S2, the composite cloth obtained in step S1 is fixed at a temperature of 200° C. for 30 seconds to obtain a cloth of a predetermined shape.

[0082] Embodiment 19: Different from Embodiment 1, in step S2, the composite cloth obtained in step S1 is fixed at a temperature of 240° C. for 60 seconds to obtain a cloth of a predetermined shape.

[0083] Example 20: Different from Example 1, in step S3, the predetermined preform of step S2 is placed in a 30°C citric acid dyeing and finishing solution, first heated to 90°C and kept warm for 15 minutes to obtain system I; system I is cooled to 60°C and maintained at this temperature for 15 minutes, during which time 5% of the weight of the composite grey cloth is added with insurance powder, and mixed to obtain system II; system II is cooled to 40°C, softener is added, and kept warm for 20 minutes.

[0084] Example 21: Different from Example 1, in step S3, the predetermined preform of step S2 is placed in a 50°C citric acid dyeing and finishing solution, first heated to 98°C and kept warm for 30 minutes to obtain system I; system I is cooled to 75°C and maintained at this temperature for 30 minutes, during which time 8% of the weight of the composite grey cloth is added with insurance powder to obtain system II; system II is cooled to 60°C, softener is added, and kept warm for 40 minutes.

[0085] Example 22: Different from Example 1, in step S6, the parameters for opening and shaping are: shaping temperature is 150°C, shaping speed is 20m / min, and shaping time is 2min.

[0086] Embodiment 23: Different from Embodiment 1, in step S6, the parameters for opening width shaping are: shaping temperature is 180°C, shaping speed is 30m / min, and shaping time is 3min.

[0087] Example 24: Different from Example 1, the preparation method of the repairable antibacterial microcapsules is as follows: first, spherical hollow nano titanium powder with a particle size of 120 to 180 μm is prepared by a soft template method, and then an antibacterial liquid is sprayed on the surface of the spherical hollow nano titanium powder to obtain an antibacterial layer with a thickness of 8 μm, and then a curing treatment is performed at a temperature of 110°C for 7 minutes, and then a repair agent A is sprayed on the surface of the antibacterial layer through a spray template A and a repair agent B is sprayed through a spray template B in sequence, wherein the antibacterial liquid comprises, by mass percentage, 70% of nano silver gel, 7% of disodium hydrogen phosphate and the remainder of sodium carboxymethyl cellulose; the repair agent A comprises, by mass percentage, 18% of nano zinc particles, 8% of carbomer, 8% of chitosan and the remainder of caprylic acid glyceride; the repair agent B is an aqueous polyurethane; the spray template A and the spray template B are each composed of a plurality of 1 cm 2The unit templates are composed of 2×2 openings evenly distributed on each unit template, and the opening diameter of the spray template A is 0.25 cm, and the opening diameter of the spray template B is 0.2 cm; the spraying method is: first spray a layer of repair agent A inside the opening of the spray template A, then remove the spray template A and adjust the position of the spray template B so that its openings are respectively located at the center of the 2×2 openings of the spray template A, and then spray a layer of repair agent B inside the opening of the spray template B; it should be noted that the spacing between the two horizontal holes and the two vertical holes of the spray template A and the spray template B is twice the spacing between the hole and the edge;

[0088] In this embodiment, the position of the spraying template B is offset 0.25 mm to the right and 0.25 mm downward from the position of the spraying template A;

[0089] Among them, during the spraying process, the distance between the nozzle and the spherical hollow nano titanium powder was 35 cm, and the spraying pressure was 0.4 MPa;

[0090] After the repair agent A is sprayed, it is placed in the irradiation box for He ion irradiation treatment. After the treatment, the repair agent B is sprayed. The irradiation energy of the He ion irradiation treatment is 360keV, the irradiation temperature is controlled at 450℃, and the injection amount is 4×10 16 cm -2 .

[0091] Example 25: Different from Example 24, the thickness of the antibacterial layer is 5 μm, and then it is cured at a temperature of 100° C. for 5 minutes, and then the repair agent A is sprayed on the surface of the antibacterial layer through the spray template A and the repair agent B is sprayed on the surface of the antibacterial layer through the spray template B.

[0092] Example 26: Different from Example 24, the thickness of the antibacterial layer is 10 μm, and then the antibacterial layer is cured at a temperature of 120° C. for 10 minutes, and then the repair agent A is sprayed on the surface of the antibacterial layer through the spray template A and the repair agent B is sprayed on the surface of the antibacterial layer through the spray template B.

[0093] Example 27: Different from Example 24, the antibacterial liquid comprises, by mass percentage, 65% of nano silver gel, 5% of disodium hydrogen phosphate and the remainder of sodium carboxymethyl cellulose; the repair agent A comprises, by mass percentage, 12% of nano zinc particles, 5% of carbomer, 5% of chitosan and the remainder of caprylic acid glyceride.

[0094] Example 28: Different from Example 24, the antibacterial liquid comprises, by mass percentage, 75% of nano silver gel, 10% of disodium hydrogen phosphate and the remainder of sodium carboxymethyl cellulose; the repair agent A comprises, by mass percentage, 25% of nano zinc particles, 10% of carbomer, 10% of chitosan and the remainder of caprylic decanoate.

[0095] Example 29: Different from Example 24, the distance between the nozzle and the spherical hollow nano-titanium powder during the spraying process is 25 cm, and the spraying pressure is 0.2 MPa.

[0096] Example 30: Different from Example 24, during the spraying process, the distance between the nozzle and the spherical hollow nano-titanium powder is 45 cm, and the spraying pressure is 0.5 MPa.

[0097] Example 31: Different from Example 24, the irradiation energy of He ions for irradiation treatment is 350keV, the irradiation temperature is controlled at 440°C, and the injection amount is 3×10 16 cm -2 .

[0098] Example 32: Different from Example 24, the irradiation energy of He ions for irradiation treatment is 370keV, the irradiation temperature is controlled at 460°C, and the injection amount is 5×10 16 cm -2 .

[0099] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.

[0100] In order to compare the effects of the present invention, the same batch of air layer second collars were used as experimental objects, and were treated by the methods corresponding to the above embodiments 1 to 32 and the comparative examples, and then the performance of the fibers after each treatment was tested. The specific comparative data are as follows;

[0101] Antibacterial effect and antibacterial stability detection: quantitative test of the effect on Escherichia coli, and judge its antibacterial property according to GB20944.3-2008-T; then the simplified washing conditions and procedures in Appendix C of FZ / T73023-2006 "Antibacterial Knitwear" were adopted for the corresponding air layer fabrics of each group, and the tested second collars were subjected to standard washing for different times. The washing conditions were: 2g / L standard synthetic washing machine, bath ratio 1:30, water temperature 40℃, put the sample in, wash for 5 minutes, and then wash with tap water at room temperature for 2 minutes, which was recorded as one wash.

[0102] 1. Explore the influence of yarn configuration on the antibacterial properties of air layer fabrics

[0103] Comparative Example 1: Different from Example 1, the conductive fibers are replaced by seaweed fibers.

[0104] Comparative Example 2: Different from Example 1, the air layer has a six-way air layer structure, and the configuration of the yarn is: the ② and ⑥ ways are connected with spandex, the ③ and ⑤ ways are connected with polyester, and the ①, ②, ③, ④, ⑤ and ⑥ ways are connected with cloth conductive fiber.

[0105] Conclusion: Figure 2-Figure 3 From the comparison of Examples 1 to 5 and Comparative Example 1, it can be seen that although the seaweed fiber also has a certain antibacterial effect and can effectively inhibit the growth of bacteria, thereby giving the fabric antibacterial properties, and the antibacterial properties of the seaweed fiber are relatively long-lasting and not easily weakened by washing, but its synergistic effect with the antibacterial masterbatch is limited, and the addition of conductive fibers helps to eliminate static electricity, thereby reducing the environment for bacterial growth. The composite material obtained by compounding with the antibacterial masterbatch not only has the antistatic function of conductive fibers, but also has the strong antibacterial properties of antibacterial materials; and the large amount of conductive fibers distributed in Comparative Example 2 will also cause the antibacterial properties of the fabric to be weakened, and the addition of conductive fibers to the antibacterial masterbatch will not only reduce the antibacterial properties of the fabric, but also reduce the antibacterial properties of the fabric. In the structure of Example 1, the polyester yarn forms a continuous thermal insulation layer in the fabric, and the distribution together with the spandex helps the fabric maintain better elasticity and fit, while providing a certain degree of thermal insulation. The addition of conductive fibers further improves the antibacterial properties of the fabric. The combination of polyester and spandex may be more conducive to forming a stable air layer, thereby improving thermal insulation, and the interaction between various routes can achieve the optimal antibacterial stability effect. However, when the conductive fibers are distributed in large quantities, it will mainly be because the conductive fibers are too dense, which will also hinder the effective release and diffusion of the antibacterial agent, thereby affecting the antibacterial effect and weakening the antibacterial stability after washing.

[0106] 2. Investigate the effect of the preparation method of antibacterial masterbatch on the antibacterial properties of air layer fabrics

[0107] Comparative Example 3: Different from Example 1, the composite liquid does not contain mineral oil.

[0108] Comparative Example 4: Different from Example 1, the repairable antibacterial microcapsules are directly loaded on the surface of the lyocell loaded with the composite liquid without using two pH adjustment and thinning treatment.

[0109] Conclusion: Figure 4-5 From the comparison of Example 1, Example 6 to Example 15 and Comparative Examples 3 and 4, it can be seen that the absence of mineral oil in the composite liquid will lead to a weakened antibacterial effect of the air layer fabric, and it is found that the antibacterial effect of the air layer fabric without mineral oil decreases significantly with the increase in the number of washing times. This is mainly because mineral oil can improve the bonding strength between graphene oxide and soluble cellulose. This stronger bonding force helps prevent graphene oxide from falling off or dispersing during use, thereby maintaining its long-term effectiveness. In Comparative Example 4, the lack of two pH adjustments and refinement treatments causes the antibacterial performance of the air layer fabric to deteriorate. This is mainly because the air layer fabric will undergo multiple washings and wear during use. If the pH value of the antibacterial masterbatch is not properly adjusted and refined, the repairable antibacterial microcapsules and graphite oxide effects will be weakened, which will be easily affected during subsequent washing and wear processes, thereby reducing the stability and durability of the antibacterial masterbatch.

[0110] 3. Explore the preparation method of repairable antibacterial microcapsules and the effect of the preparation process of air layer fabrics on the antibacterial properties of air layer fabrics

[0111] Comparative Example 5: Different from Example 24, the repair agent A does not contain carbomer.

[0112] Comparative Example 6: Different from Example 24, no He ion irradiation treatment is performed after the repair agent A is sprayed.

[0113] Conclusion: Figure 6-7 From the comparison of Example 1 and Example 16 to Example 23, it can be seen that excessively large or too small parameters in the preparation process of the air layer fabric will have a slight effect on the antibacterial performance of the air layer fabric. The state is better under the parameters of Example 1, and from the comparison of Example 1 and Example 24 to Example 31, it can be seen that the self-repairing effect of the repairable antibacterial microcapsules prepared by this scheme is better. Among them, Example 24 can achieve an antibacterial rate of 98.6% after washing 100 times in the best state, which shows that the spherical hollow nano-titanium powder has a large specific surface area and internal space, which provides a good attachment point and storage space for the subsequent spraying of antibacterial liquid and repair agent, which helps to ensure the uniformity and Stability, and it is also beneficial to maintain a certain mechanical strength and durability in the application. The antibacterial liquid is evenly sprayed on the surface of the spherical hollow nano titanium powder, and after curing treatment, it is helpful to firmly bond the antibacterial layer with the substrate, and improve the durability and stability of the antibacterial layer. The repair agent A and the repair agent B are sprayed in sequence to form a multi-layer repair system. Nano zinc particles, carbomer, chitosan and caprylic acid glyceride, these ingredients may have antibacterial effects, and water-based polyurethane can play a role in sealing and protecting the antibacterial layer, while providing additional mechanical strength and wear resistance. While ensuring the repair effect, it helps when the microcapsule is damaged. The repair agent can quickly and effectively cover the damaged area to achieve self-repairing function;

[0114] In Example 24, Example 27 to Example 28 and Comparative Example 5, the antibacterial performance of the air layer fabric obtained in Comparative Example 5 which does not contain carbomer is weakened. This is because carbomer can increase the viscosity and stability between the gel and the nano-zinc particles, effectively prolonging the duration of the action of the antibacterial components; and from the comparison of Example 24, Example 31 to Example 32 and Comparative Example 5, it can be seen that the antibacterial effect of the air layer fabric of Comparative Example 6 is also weakened compared with that of Example 24, which shows that the application of He ion irradiation treatment further improves the wear resistance, water resistance and washability of the fabric, so that the fabric can still maintain good antibacterial properties after multiple uses and washings, and the He ion irradiation treatment can further activate the surface activity of nano-titanium, promote its interaction with caprylic decanoic acid glyceride in the repairable antibacterial microcapsules, thereby enhancing the overall antibacterial effect.

[0115] In summary, the present application provides an air layer fabric with high antibacterial properties and stable antibacterial effects.

Claims

1. A warm and antibacterial air layer fabric, characterized in that: It is woven from flexible lining fabric and air layer fabric; the flexible lining fabric is woven from mulberry silk, tussah silk and castor silk through a textile machine; the air layer fabric is woven from polyester, spandex and conductive fiber in a seven-way air layer structure; the surface and interior of the flexible lining fabric and the air layer fabric are loaded with antibacterial masterbatch, and the distribution density of the antibacterial masterbatch is 35-60g / m 2 .

2. The warm and antibacterial air layer fabric according to claim 1, characterized in that: The yarn configuration of the seven air layers is as follows: the yarns of the seven air layers are sequentially recorded as ① to ⑦ from the outside to the inside, ①②③ are outer layers, ④ is a middle layer, ⑤⑥⑦ are inner layers, and the outer layer and the inner layer are symmetrically arranged along the middle layer; coil length: ② and ⑥ are 5 to 20 cm / 100 stitches, ③ and ⑤ are 22 to 28 cm / 100 stitches, ①, ④ and ⑦ are 30 to 35 cm / 100 stitches.

3. The warm and antibacterial air layer fabric according to claim 2, characterized in that: The first ①, fourth ⑦ paths are connected with spandex, the third ⑤ paths are connected with polyester, and the second ⑥ paths are connected with cloth conductive fibers; the linear density of the cloth conductive fibers is 15-25D, and the number of holes is 1-5F; the linear density of the polyester is 30-50D, and the number of holes is 50-80F; the linear density of the spandex is 20-35D, and the number of holes is 5-10F.

4. The warm and antibacterial air layer fabric according to claim 1, characterized in that: The preparation method of the antibacterial masterbatch is as follows: firstly, lyocell is immersed in a composite solution of 5 to 10 mol / L at a mass ratio of 1:2 to 6, the immersion temperature is 80 to 90°C, and the immersion time is 2 to 5 hours to obtain pretreated lyocell; the composite solution is obtained by stirring and mixing zinc nitrate hexahydrate and ethanol solution at a volume ratio of 1:1.5 to 3; Then, 2-5 mol / L caustic soda solution is added to adjust the pH of the pretreated lyocell to 7.5-8, rinse with water 2-3 times, and perform the first refinement treatment by supersonic particle bombardment at an airflow pressure of 1.8-2.4 MPa after vacuum drying. After repeating the treatment 3-5 times, prepare a composite liquid according to the mass ratio of lyocell to the composite liquid of 1:2.5-4, soak in the composite liquid at 30-40°C for 20-40 minutes, and obtain lyocell loaded with the composite liquid through drying; the composite liquid is a graphene oxide solution with a mass concentration of 5-8 mg / mL and a mineral oil with a mass concentration of 1-1.5% in a volume ratio of 1:0.2-0.3; the drying temperature is 50-70°C, and the drying time is 15-20 minutes; Then, 2-5 mol / L caustic soda solution is added to adjust the pH of the lyocell loaded with the composite solution to 8.5-9, rinsed with water 1-2 times, vacuum dried, and subjected to a second refinement treatment by supersonic particle bombardment at an airflow pressure of 3.6-4.2 MPa. After repeating the treatment 1-3 times, the repairable antibacterial microcapsules are deposited on the surface of the lyocell by magnetron sputtering to obtain the antibacterial masterbatch; during the magnetron sputtering process, the argon flow rate is 35-40 sccm, the air pressure of the vacuum chamber is 0.4-0.8 Pa, the magnetron sputtering temperature is 22-30°C, the magnetron sputtering power is 180-220 W, the deposition amount is 2-5 nm / min, and the deposition time is 30-60 s; The supersonic particle bombardment parameters are as follows: the sprayed particles are silver particles, the diameter of the sprayed particles is 20-30 μm, the bombardment time is 3-10 minutes, the air flow temperature is 40-60° C., and the bombardment distance is 10-20 mm.

5. The warm and antibacterial air layer fabric according to claim 4, characterized in that: The preparation method of the repairable antibacterial microcapsule is as follows: firstly, spherical hollow nano titanium powder with a particle size of 120-180 μm is prepared by a soft template method, then an antibacterial liquid is sprayed on the surface of the spherical hollow nano titanium powder to obtain an antibacterial layer with a thickness of 5-10 μm, and then a curing treatment is performed at a temperature of 100-120° C. for 5-10 minutes, and then a repair agent A is sprayed on the surface of the antibacterial layer through a spray template A and a repair agent B is sprayed through a spray template B in sequence, wherein the antibacterial liquid comprises, by mass percentage, 65-75% of nano silver gel, 5-10% of disodium hydrogen phosphate and the remainder of sodium carboxymethyl cellulose; the repair agent A comprises, by mass percentage, 12-25% of nano zinc particles, 5-10% of carbomer, 5-10% of chitosan and the remainder of caprylic acid glyceride; the repair agent B is an aqueous polyurethane; the spray template A and the spray template B are each composed of a plurality of nano silver gels with a surface area of ​​1 cm 2 The unit templates are composed of 2×2 openings evenly distributed on each unit template, and the opening diameter of the spray template A is 0.2-0.3 cm, and the opening diameter of the spray template B is 0.15-0.25 cm; the spraying method is: first spraying a layer of repair agent A inside the opening of the spray template A, then removing the spray template A and adjusting the position of the spray template B so that its openings are respectively located at the center of the 2×2 openings of the spray template A, and then spraying a layer of repair agent B inside the opening of the spray template B; In the spraying process, the distance between the nozzle and the spherical hollow nano titanium powder is 25 to 45 cm, and the spraying pressure is 0.2 to 0.5 MPa.

6. The warm and antibacterial air layer fabric according to claim 5, characterized in that: After the repair agent A is sprayed, it is placed in an irradiation box for He ion irradiation treatment. After the treatment, the repair agent B is sprayed. The irradiation energy of the He ion irradiation treatment is 350-370 keV, the irradiation temperature is controlled at 440-460 °C, and the injection amount is 3-5×10 16 cm -2 .

7. A process for preparing a warm and antibacterial air layer fabric according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Weaving: Place equal weights of polyester, spandex and conductive fabric on a three-position double-sided circular knitting machine and weave them in a double-sided fiber alignment method to form a woven fabric with a gram weight of 200-240g / m 2 The air layer fabric is then sewn and fixed by the flexible lining fabric and the air layer fabric to obtain a composite fabric; S2, setting the blank: setting the composite blank obtained in step S1 at a temperature of 200-240° C. for 30-60 seconds to obtain a blank of a predetermined shape; S3, dyeing: placing the predetermined parison of step S2 in a citric acid dyeing liquid at 30-50°C, first heating to 90-98°C, keeping warm for 15-30 minutes, to obtain system I; cooling system I to 60-75°C and keeping at this temperature for 15-30 minutes, during which time, adding insurance powder accounting for 5-8% of the weight of the composite grey cloth, to obtain system II; cooling system II to 40-60°C, adding softener, and keeping warm for 20-40 minutes; S4, drying: taking out the fabric treated in step S3, washing it with water, and drying it at 60-80°C; S5, shearing: performing single-side shearing on the fabric processed in step S4; S6, shaping: the fabric treated in step S5 is opened and shaped to obtain a warm and antibacterial air layer fabric.

8. The preparation process of the warm and antibacterial air layer fabric according to claim 7, characterized in that: The softener is a hydroxyl-terminated polysiloxane emulsion.

9. The preparation process of the warm and antibacterial air layer fabric according to claim 7, characterized in that: The parameters of the opening width setting are: the setting temperature is 150-180° C., the setting speed is 20-30 m / min, and the setting time is 2-3 min.